Exercise rejuvenates quiescent skeletal muscle stem cells in old mice through restoration of Cyclin D1 - Brett, Jamie O. (Nat Metab, 2020)
Aging impairs tissue repair. This is pronounced in skeletal muscle, whose regeneration by muscle stem cells (MuSCs) is robust in young adult animals but inefficient in older organisms. Despite this functional decline, old MuSCs are amenable to rejuvenation through strategies that improve the systemic milieu, such as heterochronic parabiosis. One such strategy, exercise, has long been appreciated for its benefits on healthspan, but its effects on aged stem cell function in the context of tissue regeneration are incompletely understood. Here we show that exercise in the form of voluntary wheel running accelerates muscle repair in old animals and improves old MuSC function. Through transcriptional profiling and genetic studies, we discovered that the restoration of old MuSC activation ability hinges on restoration of Cyclin D1, whose expression declines with age in MuSCs. Pharmacologic studies revealed that Cyclin D1 maintains MuSC activation capacity by repressing TGFβ signaling. Taken together, these studies demonstrate that voluntary exercise is a practicable intervention for old MuSC rejuvenation. Furthermore, this work highlights the distinct role of Cyclin D1 in stem cell quiescence.